IDENTIFICATION OF RICE PLANT DISEASES USING THE FUZZY TSUKAMOTO METHOD: IDENTIFIKASI PENYAKIT TANAMAN PADI MENGGUNAKAN METODE FUZZY TSUKAMOTO - Handayani, Sri; Rian Putra, Randi (LPPM UPMI, 2023)
Over the last few decades, the rice plant has been highly recognized as one of the strongest sources of energy for resource production. Rice plants are cultivated in five regions of the world namely Asia, Africa, America, Europe, and Oceania. Rice is crucial for humans, especially Indonesians. Most of the population of Indonesian citizens work in agriculture, generally rice. Some of the problems that attack rice plants that cause crop failure are the lack of knowledge of farmers in dealing with rice pest problems including rat pests, stem borer pests, brown planthopper pests, green leafhopper pests, golden snail pests, false white pests, ganjur pests. One of the diseases in rice plants is leaf disturbance. The types of diseases on the leaves of rice plants are very diverse, the types of diseases are well recognized by experts. After a new type of disease is identified, a solution can be given to overcome it. However, this type of disease on the leaves of rice plants is sometimes not identified by ordinary people, so that it will result in errors in identifying the type of disease and its treatment. Even experts can make identification mistakes if they are tired or in unfavorable conditions. To overcome this can be identified with computer vision. Computer vision has been widely used in identifying plant disease types. The method used to identify rice plant diseases is the Fuzzy Tsukamoto method because this method has the accuracy to detect pests through digital images. Then from this method a system design is carried out in an application software so that it can help farmers identify rice plant diseases.